2017
DOI: 10.1016/j.catena.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the structural framework on peat bog distribution in the tropical highlands of Minas Gerais, Brazil

Abstract: Peat bogs are ecosystems characterized by high levels of organic matter (OM), which accumulates in environments of low biological activity. The peat bogs present in the tropical highlands of Serra do Espinhaço Meridional (SdEM), Brazil, are associated with hydromorphic environments formed under specific conditions and the strong influence of the quartzite basement, whereby a complex pattern of faults, fractures and folds has deeply affected the drainage network and geomorphological framework. This study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
2
Order By: Relevance
“…Os aspectos geomorfológicos e climáticos na SdEM condicionam a formação de turfeiras de modo que a maioria dos córregos e rios possuem suas cabeceiras localizadas nesses ambientes. Campos et al, (2017) (Embrapa, 2013). Estes solos são constituídos por material orgânico, que apresentam horizonte hístico.…”
Section: Técnicas De Geoprocessamento Aplicadas Na Identificação De Uunclassified
See 1 more Smart Citation
“…Os aspectos geomorfológicos e climáticos na SdEM condicionam a formação de turfeiras de modo que a maioria dos córregos e rios possuem suas cabeceiras localizadas nesses ambientes. Campos et al, (2017) (Embrapa, 2013). Estes solos são constituídos por material orgânico, que apresentam horizonte hístico.…”
Section: Técnicas De Geoprocessamento Aplicadas Na Identificação De Uunclassified
“…Estes ecossistemas dependem do regime hídrico local, das condições climáticas e ambientais específicas, tais como clima de montanha. Além disso, as turfeiras atuam no sequestro de carbono da atmosfera e armazenam grandes volumes de água (Squeo et al, 2006;Silva et al, 2009a;2013a;Hórak-Terra et al, 2015;Silva e SiIva, 2017;Campos et al, 2017).…”
Section: Introductionunclassified
“…Numerous authors have shown that many factors are responsible for the geographical distribution of peatlands. Usually, the role of climate has been emphasised at global or continental scales, although the majority of authors also highlight the importance of the geomorphological and hydrological context (Charman, 2002;Montarella et al, 2006;Yu et al, 2010;Householder et al, 2012;Cubizolle et al, 2013;Page & Bird, 2016;Joosten et al, 2017;Rocha-Campos et al, 2017). Nevertheless, peatlands are difficult to classify because of their floristic diversity and their hydrological, geomorphological and even their stratigraphical and microtopographical variety (Graham et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…and are colonized by grasslands and small clusters of semi‐deciduous forest (SDF), which occupy around 6.5% of the peatland and are known locally as Capões (Silva et al , 2019). These peatlands provide important environmental services, such as carbon sequestration and water reservoirs (Silva et al , 2009, 2013; Bispo et al , 2016; Campos et al , 2016, 2017). The SdEM has one of the Earth's main areas of tropical mountain peatlands (Silva et al , 2020), which have been studied for many years (Silva et al , 2009, 2013, 2019, 2020; Horák et al , 2011; Horák‐Terra et al , 2014, 2015, 2020; Bispo et al , 2015, 2016; Campos et al , 2016, 2017), demonstrating their potential as paleoenvironmental archives (Horák et al , 2011; Horák‐Terra et al , 2014, 2015, 2020; Luz et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These peatlands provide important environmental services, such as carbon sequestration and water reservoirs (Silva et al, 2009(Silva et al, , 2013Bispo et al, 2016;Campos et al, 2016Campos et al, , 2017. The SdEM has one of the Earth's main areas of tropical mountain peatlands (Silva et al, 2020), which have been studied for many years (Silva et al, 2009(Silva et al, , 2013(Silva et al, , 2019(Silva et al, , 2020Horák et al, 2011;Horák-Terra et al, 2014Bispo et al, 2015Bispo et al, , 2016Campos et al, 2016Campos et al, , 2017, demonstrating their potential as paleoenvironmental archives (Horák et al, 2011;Horák-Terra et al, 2014Luz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%